Co-composting kinetics of rose processing waste with OFMSW - Tosun, I.; Goenuellue, M. T.; Arslankaya, E.; Guenay, A. (ELSEVIER SCI LTD, 2008)
The objective of this study was to evaluate the kinetics of co-composting of rose processing waste (RPW) and organic fraction of municipal solid waste (OFMSW). Experimental data was obtained from 65-L batch reactors. Mixtures settled up with different ratios of RPW, OFMSW, inoculation, and bulking agent. The data was consisting Of CO2 evolution and inner temperature changing with time in the reactors. Decomposition process was evaluated based on rapidly and slowly biodegradable fractions of organic matter. The experimental data has been analyzed by kinetic models including the first-zero-order, first-first-order, Chen and Hashimoto's and Levi-Minzi's kinetic models using non-linear regression techniques. Kinetic parameters and rate constants were evaluated based on the average relative errors and coefficient of determination. The results of study showed that the best fitting kinetic model is the first-first-order. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: composting kinetics; rose processing waste; CO2 evolution; MUNICIPAL SOLID-WASTE; CARBON MINERALIZATION; DEGRADATION; SLUDGE; WATER; RECIRCULATION; AERATION; FRACTION; BATCH; MODEL; Agriculture; Biotechnology & Applied Microbiology; Energy & Fuels